THE EFFECT OF REFLECTIVE JOURNAL WRITING ON STUDENTS’ WRITING ABILITY OF NARRATIVE TEXT AT THE TENTH GRADE STUDENTS OF MAS AL WASHLIYAH 29 BINJAI - Nudia Yultisa; Dewi Rulia Sitepu; Tri Indah Rezeki; Susi Anggraini; Efrini Panjaitan (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
The study deals with an experimental research design which seeks for the effect of reflective journal writing on students’ writing ability of narrative text. 52 students at the tenth grade students of MAS Al Washliyah 29 Binjai on the first semester were taken as the samples of the study. Pre-test and post-test as the written test were given to measure whether the reflective journal writing had a significant effect toward the students’ writing ability of narrative text or not. The final data then was analyzed by using Paired-Samples T Test analysis shown that the significance (sig) 2-tailed value 0.000000 was lower than the significance level (0.05) and determined that coefficient of tcounted was 18.682 signifying higher than the ttable coefficient (2.05954) with significance level (α) = 0.025 (2-tailed) with degree of freedom (df) = 25. This means that there is a significant effect of reflective journal writing on students’ writing ability of narrative text at the tenth-grade students of MAS Al Washliyah 29 Binjai. Therefore, Ha was accepted and H0 was rejected.